Revisiting Management Strategies for Popliteal Artery Injuries. (1st March 2022) - Lin, Cen-Hung; Consuegra, Ma. Dulce Lafuente; Lin, Tsan-Shiun
Abstract : Background: Popliteal artery injuries (PAIs) were reported to own the highest rates of limb loss in vascular injuries of extremities. The complex nature of PAIs makes the treatment more difficult. We aimed to present our cases using our proposed algorithm and revisit the strategies for management. Patients and Methods: A retrospective study of 45 cases with PAIs managed at the Kaohsiung Chang Gung Memorial Hospital over a 10-year period was conducted. The proposed algorithm for decision making was applied, which contains variables including the interval before surgery, the revascularization being delayed or not, the presence of fasciotomy, the acquisition of preoperative angiography, and the existence of collateral circulation. Whether the injured limbs were salvaged successfully avoiding amputation was recorded. Results: Of all the included 45 patients, the rate of a successful salvage of the injured limb from amputation was 71.1%. Six patients did not receive revascularization because of their poor conditions of the injured limbs. In terms of limb salvage in PAIs, the interval before surgery, the revascularization being delayed or not, the presence of fasciotomy, or the acquisition of preoperative angiography did not make a significant difference ( P > 0.05). Instead, an existence of collateral circulation at the distal injured limb was correlated to a significant higher rate of salvage, regardless of having revascularization or not ( P = 0.001 and < 0.001, respectively). Seven patients had the injured vessels repaired directly and all were prevented from amputation. In other patients who underwent vascular repair using a graft, vein graft (n = 20) showed a higher successful rate in salvage significantly than Gore-Tex graft (n = 9, P < 0.001). Conclusions: Collateral circulation determines much of the fate of limb salvage in PAIs. As a result, a delayed revascularization could be accepted as long as there is existence of collateral circulation at the distal injured limb. An autologous vein graft is favored when a direct repair is not able to be performed for revascularization. Although fasciotomy was not found to be associated with a successful salvage in this study, its importance could not be neglected and it should be performed when there is an observed or impending compartment syndrome.